PO043 Efficacy of eslicarbazepine acetate versus controlled-release carbamazepine as monotherapy in patients with newly diagnosed partial-onset seizures. (1st December 2017) - Ben-Menachem, E; Trinka, E; Kowacs, P; Elger, C; Moreira, J; Pinto, R; Ikedo, F; Pereira, A; Rocha, JF; Soares-da-Silva, P
Abstract : Purpose: This phase-III, randomised, double-blind, active-controlled, non-inferiority study aimed to demonstrate the efficacy and safety of once-daily (QD) ESL as monotherapy treatment for newly diagnosed adults with POS in comparison to twice-daily (BID) controlled-release carbamazepine (CBZ-CR). Method: Patients (≥18 years) were randomised (1:1) to receive ESL or CBZ-CR in a 3-step dose-level design. Each dose-level was maintained through a 26 week Evaluation-Period (EP). Subjects who remained seizure-free at any dose-level continued through subsequent periods/phases. Primary-endpoint was proportion of patients with 26 week seizure freedom in the per-protocol (PP) population. Results: 815 patients were randomised (PP population; ESL n=388; CBZ-CR n=397). In the PP population, the proportion of subjects classified as seizure-free for the entire 26 week Evaluation Period at the last evaluated dose was comparable between the ESL group (71.1%) and the CBZ-CR group (75.6%) and ESL was shown to be non-inferior to CBZ-CR. Results from the sensitivity analyses were consistent with the primary analysis results. ESL was non-inferior to CBZ-CR during 1 year of treatment, as the 1 year seizure-free rate at the last evaluated dose (PP population) was 64.7% on ESL group and 70.3% on CBZ-CR group. Conclusion: ESL QD was non-inferior to CBZ-CR BID for seizure freedom rates in patients with newly diagnosed epilepsy. Sponsored by BIAL-Portela and Cª S.A.